Nanopartículas de sílica mesoporosa recobertas com quitosana para liberação de moléculas bioativas controlada por PH - Ferreira, Mariana Mendonca [UNIFESP] (2018)
The interest in nanomaterials capable of acting in drug release processes has increased in the last decade specially the ones that involve drugs with administration restrictions. In this field, mesoporous silicas have been considered one of the most promising inorganic systems due to their unique chemical, structural and biological properties such as: chemical and structural stability in the physiological medium, high surface area, easy chemical modification, biocompatibility, biodegradability and low toxicity. In this study, mesoporous silica nanoparticles were coated with a chitosan layer in order to generate a hybrid nanoparticle capable of controlling the release of bioactive molecules by a process triggered by the acidification of the medium. Chitosan is a semi synthetic biopolymer, which due to its renewable origin and its processing in aqueous medium is considered sustainable, with interesting properties such as low toxicity, bactericidal activity, biocompatibility and biodegradability that are useful for biomedical applications. As the amino groups (pKa = 6.5) of the polymeric chain can be protonated in diluted acidic medium, at neutral or basic pH it is expected that the entanglement among the polymeric chains block the release of drugs previously immobilized into the silica pores. Whereas under acid pH, the protonation of these groups can promote conformational changes to the polymeric chains due to electrostatic repulsion that triggers the drug release. Different synthetic routes were evaluated in order to coat the mesoporous silica nanoparticles with chitosan by formation of covalent bonds between these moieties. The best result was achieved by coating the silica nanoparticles through the formation of imines bonds between amino groups present in a post-functionalized silica nanoparticle and in the chitosan promoted by glutaraldehyde, used as crosslinking agent. In this study, fluorescein was used as a model molecule for the evaluation of controlled release capabilities due to its optical properties that enable its easy spectrophotometric monitoring. The rate of release in acid medium was higher than in neutral or basic medium and the kinetics mechanism was dependent on the diffusion of the species through the pores. The produced hybrid nanoparticles presented sizes adequate to be captured by cells through endocytosis and showed drug release mechanism triggered by acidic pH which are required characteristics for their further use in intracellular release of bioactive species.